Sintomas Neuropsiquiátricos na Demência Frontotemporal Variante Comportamental e seu Impacto na Cognição Social - Lucas de Andrade Saraiva (2025)
INTRODUCTION: Neuropsychiatric symptoms (NPS) are highly prevalent in patients with dementia syndromes, which can pose challenges in diagnosing and managing behavioral variant frontotemporal dementia (bvFTD). There are still gaps in the literature regarding the frequency of NPS in bvFTD. Furthermore, studies evaluating the impact of NPS on social cognition tests in bvFTD patients are limited. OBJECTIVES: To assess the frequency and correlations of neuropsychiatric symptoms with social cognition tests (Theory of Mind and facial emotion recognition) in bvFTD patients, comparing them with Alzheimer’s disease (AD) patients. METHODS: Two groups were included: 1) bvFTD (n = 13; 7F/6M; age = 66.0 years; education = 11.0 years) and 2) AD (n = 18; 6F/12M; age = 71.5 years; education = 11.0 years). The neuropsychiatric assessment used the Montgomery-Asberg Depression Rating Scale (MADRS), Hamilton Anxiety Rating Scale (HAM-A), Young Mania Rating Scale (YMRS), Obsessive-Compulsive Inventory-Revised (OCI-R), Positive and Negative Syndrome Scale (PANSS), Cambridge Behavioral Inventory-Revised (CBI-R), Starkstein Apathy Scale, and the Pfeffer Functional Activities Questionnaire (PFEFFER). All participants underwent a comprehensive cognitive evaluation, which included the Mini-Sea battery for assessing Theory of Mind and facial emotion recognition. RESULTS: The groups did not differ in sex, education, family income, or disease duration. The Mini-Mental State Examination (MMSE) scores were similar for both the frontotemporal dementia (FTD) group (MMSE = 25.0) and the AD group (MMSE = 24.0). Patients with bvFTD had higher total scores on the PANSS compared to patients with AD (p < 0.001). Additionally, individuals with bvFTD exhibited more severe negative symptoms (p < 0.001) and general psychopathology symptoms (p < 0.001) than those in the AD group. Furthermore, a higher prevalence of manic symptoms, as measured by the YMRS, was observed in patients with bvFTD compared to those with AD (p < 0.001). There were moderate-to-strong correlations between neuropsychiatric symptoms and social cognition test scores, with distinct patterns for the bvFTD and AD groups. In the bvFTD group, significant correlations were found between depressive (ρ=0,624; p=0,020), anxious (ρ=0,614; p=0,045), and positive psychotic symptoms (ρ=-0,778; p=0,005) and performance on social cognition tests. In the AD group, significant correlations were identified between anxious symptoms (ρ=-0,583; p=0,047), manic symptoms (ρ=-0,551; p=0,033), obsessive-compulsive symptoms (ρ=-0,688; p=0,013), disorganized psychotic symptoms (ρ=-0,712; p=0,009), and performance on social cognition tests. CONCLUSIONS: bvFTD patients exhibited more psychotic and manic symptoms compared to patients with AD. These findings are significant for the clinical differentiation between bvFTD and AD. Additionally, our results suggest a distinct impact of neuropsychiatric symptoms on behavior and social cognition in patients with bvFTD and AD. Finally, a larger sample size is necessary for better characterization of neuropsychiatric symptoms in bvFTD and AD, as well as for a deeper understanding of their influence on social cognitive performance in these diseases.